2017
DOI: 10.14738/assrj.44.2064
|View full text |Cite
|
Sign up to set email alerts
|

Risk Tolerance, Impulsivity, and Self-esteem: Differences and Similarities between Gamblers and Non-Gamblers in a Pilot Study

Abstract: Risk-taking ranges from socially beneficial entrepreneurship through games of chance as entertainment to problem gambling that can be both individually and socially destructive. There are many conflicting theories about what leads individuals to become gamblers, although some consensus suggests a link to personality traits. Links between gambling and impulsivity, risk tolerance and self-esteem remain unclear, and childhood experiences may be pertinent. To explore these issues, we studied 41 non-gamblers and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…Bonnaire et al ( 2017 ) also found higher levels of depression in pathological gamblers when compared with non-pathological gamblers, whereas Maniaci et al ( 2017 ) found a greater tendency to show negative emotional states such as anger. Nevertheless, another study, conducted by Suen et al ( 2017 ), found significant differences between non-problem and problem gamblers in variables such as impulsivity and risk-tolerance, whereas Jara-Rizzo et al ( 2019 ) highlighted the potential relationship between affect-mediated impulsivity and gambling-related cognitions in gamblers. In the same line, other studies have found greater levels of alexithymia in university students with problem gambling behavior in comparison with non-problem gamblers (Parker et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bonnaire et al ( 2017 ) also found higher levels of depression in pathological gamblers when compared with non-pathological gamblers, whereas Maniaci et al ( 2017 ) found a greater tendency to show negative emotional states such as anger. Nevertheless, another study, conducted by Suen et al ( 2017 ), found significant differences between non-problem and problem gamblers in variables such as impulsivity and risk-tolerance, whereas Jara-Rizzo et al ( 2019 ) highlighted the potential relationship between affect-mediated impulsivity and gambling-related cognitions in gamblers. In the same line, other studies have found greater levels of alexithymia in university students with problem gambling behavior in comparison with non-problem gamblers (Parker et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…Impulsivity, a personality trait which refers to hasty and inappropriate behavior is also considered to influence the severity of gambling-related problem [ 10 , 11 , 12 , 13 ]. Impulsive characteristics and gambling-related cognitions are recognized as two major psychological factors in the emergence and retention of problem gambling [ 14 ]. A meta-analysis on the relationship between impulsivity and problem gambling showed that intensified impulsive choice, impulsive motor responses, impulsive decision-making, reflection impulsivity, and impulsive cognitive bias are related to gambling disorders; moreover, impulsive decision-making may extend to problem gambling [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…As previously mentioned, 2DMSE explained that SE is an integrated sum of self-worth and selfcompetence [27], [28]; therefore, its adequacy is significant for every individual. It has been said to be the factor of adequate academic achievements [43], success of teaching and learning [44], risk tolerance in entrepreneurship [45], and even the way individuals choose the course of action in entrepreneurship; individuals with dominant self-worth tend to pursue opportunities in Kirnzerian way, while those with dominant self-competence tend to pursue opportunities in Schumpeterian way [25].…”
Section: Self-esteemmentioning
confidence: 99%